Unveiling the proton spin decomposition at a future electron-ion collider - Aschenauer, Elke Caroline (2015)
We present a detailed assessment of how well a future Electron-Ion Collider could constrain helicity parton distributions in the proton, and therefore unveil the role of the spin of quarks and gluons, as well as that of their orbital angular momentum, in the proton spin budget. Specifically, this is done in the light of the most recent polarized proton-protoncollision data obtained at BNL-RHIC, that suggest a significant contribution of the gluon spin, and have modified considerably our picture of the gluon helicity distribution in QCD global analyses.